Environmental and occupational exposure to benzene by analysis of breath and blood. Issue 5 (May 1988) - Perbellini, L; Faccini, G B; Pasini, F; Cazzoli, F; Pistoia, S; Rosellini, R; Valsecchi, M; Brugnone, F
Abstract : Benzene exposure of chemical workers was studied, during the entire workshift, by continuous monitoring of workplace benzene concentration, and 16 hours after the end of the workshift by the measurement of alveolar and blood benzene concentrations and excretion of urinary phenol. Exposure of hospital staff was studied by measuring benzene concentrations in the alveolar and blood samples collected during the hospital workshift. Instantaneous environmental air samples were also collected, at the moment of the biological sampling, for all the subjects tested. A group of 34 chemical workers showed an eight hour exposure to benzene, as a geometric mean, of 1.12 micrograms/l which corresponded, 16 hours after the end of the workshift, to a geometric mean benzene concentration of 70 ng/l in the alveolar air and 597 ng/l in the blood. Another group of 27 chemical workers (group A) turned out to be exposed to an indeterminable eight hour exposure to benzene that corresponded, the morning after, to a geometric mean benzene concentration of 28 ng/l in the alveolar air and 256 ng/l in the blood. The group of hospital staff (group B) had a benzene concentration of 14 ng/l in the alveolar air and 269 ng/l in the blood. Instantaneous environmental samples showed that in the infirmaries the geometric mean benzene concentration was 58 ng/l during the examination of the 34 chemical workers, 36 ng/l during the examination of the 27 chemical workers (group A), and 5 ng/l during the examination of the 19 subjects of the hospital staff (group B). Statistical analysis showed that the alveolar and blood benzene concentrations in the 34 workers exposed to 1.12 microgram/l of benzene differed significantly from those in groups A and B. It was found, moreover, that the alveolar and blood benzene concentrations were higher in the smokers in groups A and B but not in the smokers in the group of 34 chemical workers. The slope of the linear correlation between the alveolar and the instantaneous environmental benzene concentrations suggested a benzene alveolar retention of about 55%. Blood and alveolar benzene concentrations showed a highly significant correlation and the blood/air partition coefficient, obtained from the slope of the regression line, was 7.4. In the group of the 34 chemical workers no correlation was found between the TWA benzene exposure and the urinary phenol excretion.